Responses of Selected Inflammatory, Kidney and Liver Function Markers in Serum of Nigerian Children with Severe Falciparum Malaria to Treatment with Artesunate/Artemether-Lumefantrine Combination Therapy (African Journal of Biomedical Research, 2019)
Malaria tolerance is a defence strategy that limits the damage caused by Plasmodium species irrespective of pathogen burden. The mechanisms responsible for this, responses of these mechanisms and their impact on organs to treatment have not been extensively studied. Thus, in this study, serum levels of selected pro- and anti-inflammatory markers, liver and kidney function indices with leucocytes indices in 100 children (1-10 years) with severe falciparum malaria were determined before treatment, at 48 hours during treatment and 48 hours after treatment with WHO recommended dosage of artesunate/artemether-lumefantrine combination therapy using standard methods. Data were analysed using SPSS, differences were considered significant at p
Keywords: Immunity; falciparum malaria; inflammatory markers; children